2019
DOI: 10.1177/0038038519853146
|View full text |Cite
|
Sign up to set email alerts
|

The Methodological Divide of Sociology: Evidence from Two Decades of Journal Publications

Abstract: Past research indicates that Sociology is a low-consensus discipline, where different schools of thought have distinct expectations about suitable scientific practices. This division of Sociology into different subfields is to a large extent related to methodology and choices between qualitative or quantitative research methods. Relying on theoretical constructs of the academic prestige economy, boundary demarcation and taste for research, we examine the methodological divide in generalist Sociology journals. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 59 publications
2
33
0
11
Order By: Relevance
“…Similarly, the methodological focuses of environmental articles have also been observed in the dichotomies. Owing to the less focus and greater on quantitative methods our study confirms the methodological divide of Schwemmer and Wieczorek (2019) in the field of environmental Sociology with respect to our six journals. It has been observed in various literatures that in the USA there is much emphasis on the quantitative strand of methodologies while UK with qualitative (see also Kerlin 2000;Bryman 2008;Payne, Williams & Chamberlain 2004;and Gage 1989).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly, the methodological focuses of environmental articles have also been observed in the dichotomies. Owing to the less focus and greater on quantitative methods our study confirms the methodological divide of Schwemmer and Wieczorek (2019) in the field of environmental Sociology with respect to our six journals. It has been observed in various literatures that in the USA there is much emphasis on the quantitative strand of methodologies while UK with qualitative (see also Kerlin 2000;Bryman 2008;Payne, Williams & Chamberlain 2004;and Gage 1989).…”
Section: Discussionsupporting
confidence: 75%
“…Studies provide us with handful evidences that still there is a clear dividing line between the two methodological orientations (Quantitative and Qualitative) across national and international sociologists. For example, Schwemmer and Wieczorek (2019) have ascertained methodological divide in Sociology by analyzing 8737 abstracts of papers from 1995-2017. They also find out a high time trend of utilization for quantitative methodologies.…”
Section: Methodological Dividementioning
confidence: 99%
“…The four top-tier generalist journals in our sample -ASR, AJS, SOC, BJS -differ considerably in their methodological preferences. Existing studies have shown that SOC and BJS are the most qualitative among the generalist sociology journals while ASR and AJS can be considered as rather quantitative (Baer, 2005;Schwemmer and Wieczorek, 2020). However, since we only look at the four top-tier journals it is indeed possible that qualitative and conceptual works are still common in second ranked sociology journals.…”
Section: Discussionmentioning
confidence: 97%
“…Daenekindt and Huisman (2020) analysed the field of higher education using correlated topic modelling (Blei and Lafferty 2007), which allowed the authors to compare 17,000 abstracts published in journals in the field of higher education research. Schwemmer and Wieczorek (2020) studied the methodological divergence in sociology between quantitative and qualitative analysis in more than 8700 research articles in top journals of the field, using the wordfish model (Slapin and Proksch 2008). Another study analysed more than 20 million article titles to investigate the expansion of cognitive boundaries in physics, astronomy, and biomedicine.…”
Section: Introductionmentioning
confidence: 99%